Spiritual well-being and mental health among Malaysian adolescents - Yahaya, Nurizan; Momtaz, Yadollah Abolfathi; Othman, Mumtazah; Sulaiman, Norhasmah; Mat Arisah, Farhan (Marsland Press, 2012)
Background: Adolescents are vulnerable to various mental health problems. The existing body of knowledge on the role of spirituality on adolescents’ mental health status is limited and disjointed. The main aim of this study was to examine impact of spirituality on adolescents’ mental health problems, after controlling for possible sociodemographic factors. Method: A total of 1190 Malaysian adolescents selected through a multistage proportional stratified random technique from the Federal Territory of Kuala Lumpur and Selangor state filled out questionnaires including the Spiritual Well-Being Scale, the General Health Questionairre-28 (GHQ-28), and sociodemographic characteristics. A two step hierarchical multivariate logistic regression using SPSS software for Windows (SPSS Inc., Chicago, Ill., USA) was employed to test hypothesis. Results: Using the recommended cut-off point of 6 or more for the total GHQ-28, the prevalence rate of possible mental health problems was calculated 54.6% (CI 95%: 51.8 to 57.4 ). The findings from hierarchical multivariate logistic regression showed existential well-being (OR =0.42, p≤.001, 95% CI: 0.32–0.54) and religious well-being (OR =0.63, p≤.01, 95% CI: 0.47–0.85) were statistically associated with 58% and 37% lower odds of mental health problem, respectively, over and above sex, living arrangements of adolescents, parental education and household income. Conclusion: The present study found noticeable rates of mental health problems among Malaysian adolescents and pointed out the importance of spirituality as a resilience factor might help children to cope with physiologic, physical and psychological changes through adolescence, successfully.